B (at) PDA (at) Viton composite particle and preparation method thereof
By forming the coating structure of B@PDA@Viton composite particles on the surface of the boron powder, the problem of low boron ignition combustion performance and energy release efficiency in the prior art is solved, and more efficient energy release and more uniform coating effect are achieved.
Patent Information
- Application Number
- CN202311272191.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-28
- Publication Date
- 2025-03-07
AI Technical Summary
In the existing boron coating modification technology, the ignition combustion performance and energy release efficiency of boron are not high, and the coating layer is prone to fall off and uneven coating.
The preparation method of B@PDA@Viton composite particles is adopted to prepare B@PDA composite particles by a one-pot method in deionized water, and secondary coating of Viton fluoroelastomer is performed on their surface to form a denser and uniform coating layer.
It significantly improves the ignition combustion performance and energy release efficiency of boron, avoids the easy shedding and unevenness of the cladding layer, and is easy to obtain raw materials and cheap prices, and the preparation method is simple and controllable.
Smart Images

Figure CN119569516A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of energetic material preparation, and specifically relates to B@PDA@Viton composite particles and a preparation method thereof. Background Art
[0002] Boron (B) is a high-energy metal fuel with a mass calorific value of 58.74 kJ / g and a volume calorific value of 137.24 kJ / cm 3 , which are 1.90 times and 1.64 times that of Al, respectively. Therefore, boron has broad application prospects in high-energy metal fuels. Although the theoretical calorific value of boron is very high, there is a boron oxide (B2O3) layer with a low melting point (450°C) and a high boiling point (1860°C) on the surface of boron. During the ignition and combustion process of boron, it will become a layer of viscous liquid that wraps the boron, resulting in an increase in the ignition delay time of boron and a decrease in the energy release efficiency. In order to solve these problems, the surface of boron can be coated to improve the ignition and combustion reaction of boron. When the surface of boron is coated with a fluorine-containing polymer, the fluorine-containing substance generated by the thermal decomposition of the fluorine-containing polymer can react with boron oxide to generate gas, thereby improving the energy release efficiency of boron.
[0003] In recent years, polydopamine (PDA) has become an important research direction in the field of surface modification due to its unique adhesion properties. PDA can functionalize the surface of most substrates and improve interfacial properties. In addition, the polymerization conditions of PDA are simple, the process is controllable, and a large number of hydroxyl and amine functional groups can be introduced on the surface of the material after surface coating. It can be used as a secondary reaction platform to graft other functional molecules and polymers again. It has broad application prospects in the preparation of composite materials. In the existing boron coating modification technology research, boron powder coated with perfluoropimelic acid (PFPA) and polytrifluorochloroethylene (PCTFE) has been prepared. Fluoropolymers reduce the agglomeration of boron combustion products and increase the specific surface area of boron, but the thermal reaction performance of boron has not been significantly improved. Qin et al. prepared a composite film of micron boron powder and polyvinylidene fluoride (PVDF) in "Preparation and characterization of energetic composite films with mutual reactions based on B / PVDF mosaic structure" in Chemical Engineering Journal, 2023, but the boron content in the composite film is low and the specific surface area of the membrane structure is small, thereby reducing the total energy of the system. In addition, the existing methods mainly use fluorine-containing polymers for coating, which has the problem of easy detachment of the coating layer and uneven coating. Summary of the invention
[0004] In view of the defects and shortcomings of the prior art, the purpose of the present invention is to provide a B@PDA@Viton composite particle and a preparation method thereof, so as to solve the technical problems of low boron ignition combustion performance and low energy release efficiency in the existing boron coating modification technology.
[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions to achieve the above problems:
[0006] A method for preparing B@PDA@Viton composite particles, characterized in that it comprises the following steps:
[0007] Step 1, mixing boron powder with deionized water, stirring at 70-90° C. for 4-6 hours to obtain a boron powder dispersion;
[0008] Step 2, adding tris(hydroxymethyl)aminomethane to deionized water to prepare a Tris buffer solution with a pH of 8 to 9;
[0009] Step 3, adding dopamine hydrochloride and the boron powder dispersion prepared in step 1 to the Tris buffer solution prepared in step 2, stirring and reacting at room temperature for 12 to 24 hours, and then filtering and drying to obtain B@PDA composite particles;
[0010] Step 4, adding the B@PDA composite particles obtained in step 3 into an organic solvent, stirring at room temperature for 20 to 30 minutes to obtain a B@PDA dispersion;
[0011] Step 5: dissolve Viton fluororubber in a low boiling point solvent to obtain a Viton fluororubber solution, add the Viton fluororubber solution to the B@PDA dispersion obtained in step 4 at 45-55° C., stir and react for 4-7 hours, and obtain B@PDA@Viton composite particles by suction filtration and drying.
[0012] The present invention also has the following technical features:
[0013] Furthermore, the particle size of the boron powder in step 1 is 1 to 10 μm.
[0014] Furthermore, the mass ratio of the boron powder in step 1 to deionized water is 1:(60-80).
[0015] Furthermore, the mass ratio of the tris(hydroxymethyl)aminomethane described in step 2 to the micron boron powder used is 1:(8-17).
[0016] Furthermore, in step 3, the mass ratio of dopamine hydrochloride to boron powder is 1:(2-5).
[0017] Furthermore, the mass ratio of the B@PDA composite particles to the organic solvent in step 4 is 1:(40-60).
[0018] Furthermore, the organic solvent described in step 4 includes n-octane, n-heptane, n-decane, undecane, and dodecane.
[0019] Furthermore, the mass ratio of the Viton fluororubber to the low boiling point solvent in step 5 is 1:
[0020] (100~300); the mass ratio of Viton fluororubber to B@PDA composite particles is 1:(10~50).
[0021] Furthermore, the low boiling point solvent in step 5 includes acetone, ethyl acetate, methyl ethyl ketone, and tetrahydrofuran.
[0022] The present invention also protects a B@PDA@Viton composite particle, wherein the composite particle is prepared by the above-mentioned method for preparing the B@PDA@Viton composite particle.
[0023] Compared with the prior art, the present invention has the following beneficial technical effects:
[0024] (1) The method of the present invention pre-treats the boron powder to remove the oxide film, thereby improving the activity of the boron powder. The PDA is coated on the surface of the boron by a one-pot method, thereby avoiding the secondary oxidation of the boron powder during the treatment process, which is beneficial to maintaining the activity of the boron powder. The interaction between boron and fluorine is enhanced by the PDA modified layer. The fluororubber decomposes at high temperature to release HF and other fluorine-containing substances. These react with boron to release higher heat and generate BF3 gas, thereby improving the reaction performance of boron and significantly improving the ignition and combustion performance of boron.
[0025] (2) The raw materials of the present invention are easily available and inexpensive, and the preparation method is simple and controllable, which is conducive to large-scale preparation and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a schematic diagram of the preparation process of the B@PDA@Viton composite particles of the present invention.
[0027] Figure 2 This is the ATR-FTIR spectrum of the micron boron powder of the present invention and the B@PDA@Viton composite particles prepared in Example 1.
[0028] Figure 3 This is a TEM image of the boron powder with the surface film removed obtained in step 1 of Example 1 of the present invention.
[0029] Figure 4 This is a TEM image of the B@PDA composite particles prepared in Example 1 of the present invention.
[0030] Figure 5 This is a TEM image of the B@PDA@Viton composite particles prepared in Example 1 of the present invention.
[0031] The technical solution of the present invention is further described below in conjunction with embodiments. DETAILED DESCRIPTION
[0032] In accordance with the above technical scheme, specific embodiments of the present invention are given below. It should be noted that the present invention is not limited to the following specific embodiments, and all equivalent changes made on the basis of the technical scheme of this application fall within the protection scope of the present invention.
[0033] The technical concept of the present invention is: using the principle that the oxide layer on the surface of the boron powder can be dissolved and removed in deionized water, and dopamine hydrochloride can be polymerized in situ to generate polydopamine, the B@PDA composite particles are prepared in a one-pot method in deionized water, thereby avoiding the secondary oxidation of the boron powder in contact with air when preparing the composite particles. After PDA coating, multiple hydroxyl active sites are formed on the surface of the boron powder, which helps to anchor other functional groups again, and then Viton fluororubber is used for secondary coating again, and the F atoms form hydrogen bonds with the hydroxyl groups, making the Viton coating more dense and uniform. The obtained B@PDA@Viton composite particles have better ignition and combustion performance than the boron-fluorine composite particles prepared by traditional methods.
[0034] The present invention provides a method for preparing B@PDA@Viton composite particles, comprising the following steps:
[0035] Step 1, mixing boron powder with deionized water, stirring at 70-90° C. for 4-6 hours to dissolve the oxide layer on the surface of the boron powder, and obtaining a boron powder dispersion;
[0036] Preferably, the particle size of the boron powder is 1 to 10 μm.
[0037] Preferably, the mass ratio of the boron powder to deionized water is 1:(60-80).
[0038] Step 2, adding tris(hydroxymethyl)aminomethane to deionized water to prepare a Tris buffer solution with a pH of 8 to 9;
[0039] Preferably, the mass ratio of tris(hydroxymethyl)aminomethane to the micron boron powder is 1:(8-17);
[0040] Step 3, adding dopamine hydrochloride and the boron powder dispersion prepared in step 1 to the Tris buffer solution prepared in step 2, stirring and reacting at room temperature for 12 to 24 hours, and then filtering and drying to obtain B@PDA composite particles;
[0041] Preferably, the mass ratio of dopamine hydrochloride to boron powder is 1:(2-5).
[0042] Step 4, adding the B@PDA composite particles obtained in step 3 into an organic solvent, stirring at room temperature for 20 to 30 minutes to obtain a B@PDA dispersion;
[0043] Preferably, the mass ratio of the B@PDA composite particles to the organic solvent is 1:(40-60).
[0044] Preferably, the organic solvent includes n-octane, n-heptane, n-decane, undecane and dodecane.
[0045] Step 5: dissolve Viton fluororubber in a low boiling point solvent to obtain a Viton fluororubber solution, add the Viton fluororubber solution to the B@PDA dispersion obtained in step 4 at 45-55° C., stir and react for 4-7 hours, and obtain B@PDA@Viton composite particles by suction filtration and drying.
[0046] Preferably, the mass ratio of the Viton fluororubber to the low boiling point solvent is 1:(100-300); the mass ratio of the Viton fluororubber to the B@PDA composite particles is 1:(10-50).
[0047] Preferably, the low boiling point solvent includes acetone, ethyl acetate, methyl ethyl ketone and tetrahydrofuran.
[0048] The boron powder used in the present invention is produced by Yingkou Liaobin Fine Chemical Co., Ltd. The Viton fluororubber is FKM26 series, produced by Shandong Dongyue Chemical Co., Ltd., and reagents such as tris(hydroxymethyl)aminomethane, dopamine hydrochloride, cyclohexane, n-heptane, and acetone are commercially available products of Aladdin Reagent (Shanghai) Co., Ltd., and the purity specifications are all analytically pure.
[0049] Example 1
[0050] In accordance with the above technical solution, this embodiment discloses a method for preparing B@PDA@Viton composite particles, comprising the following steps:
[0051] Step 1, adding 1.50 g of boron powder with a particle size of 1 to 10 μm to 60 g of deionized water, stirring at 80° C. for 6 h to obtain a boron powder dispersion;
[0052] Step 2, adding 0.121 g of tris(hydroxymethyl)aminomethane to 100 g of deionized water to prepare a Tris buffer solution with a pH of 8.5;
[0053] Step 3: Add 0.6 g of dopamine hydrochloride and the boron powder dispersion prepared in step 1 to the Tris buffer solution prepared in step 2, stir at room temperature for 24 h, filter, dry, and weigh to obtain 1.45 g of B@PDA composite particles.
[0054] Step 4, taking 1 g of the B@PDA composite particles obtained in step 3, adding them to 60 g of n-heptane, stirring at room temperature for 20 to 30 min, and mixing them evenly to obtain a B@PDA dispersion;
[0055] Step 5: Dissolve 0.02 g of Viton fluororubber in 6 g of acetone to obtain a fluororubber solution, add the solution to the B@PDA dispersion obtained in step 4 at 45°C, stir for 4 h, filter, dry, and weigh to obtain 0.98 g of B@PDA@Viton composite particles.
[0056] The structure of the prepared B@PDA@Viton composite particles was identified, and the following results were obtained:
[0057] Infrared spectrum analysis
[0058] like Figure 2 As shown in the figure, the prepared B@PDA@Viton composite particles have a -1 and 1271.3cm -1 The characteristic peaks of C=N bond and CN bond appeared at 882cm -1 The characteristic peak of CH2=CF2 in polyvinylidene fluoride appeared at , indicating that the B@PDA@Viton composite particles were successfully prepared in this example.
[0059] Morphology analysis
[0060] like Figure 4 and Figure 5 As shown in the figure, after surface film removal, the surface of the boron powder is smooth and does not contain an oxide layer. After PDA modification, it can be observed that there is a PDA-modified coating layer of about 1 nm on the surface of the boron powder, and the surface is rougher. The specific surface area of the boron particles is increased, which helps to improve the reaction activity of boron. After being coated with fluororubber, the surface of the boron is coated with a layer of flocculent fluororubber, and it is filled between the boron particles, avoiding direct contact and agglomeration of the boron powder.
[0061] Example 2
[0062] The steps of the preparation method of fluororubber-coated boron composite particles disclosed in this embodiment are the same as those in Example 1, with the only difference being that the amount of dopamine hydrochloride used is different. In this embodiment, the amount of dopamine hydrochloride used in step 3 is 0.30 g, and 0.99 g of B@PDA@Viton composite particles are finally obtained.
[0063] Example 3
[0064] The steps of the preparation method of fluororubber-coated boron composite particles disclosed in this embodiment are the same as those in Example 1, with the only difference being that the amount of dopamine hydrochloride used is different. In this embodiment, the amount of dopamine hydrochloride used in step 3 is 0.45 g, and 0.98 g of B@PDA@Viton composite particles are finally obtained.
[0065] Example 4
[0066] The steps of the preparation method of fluororubber-coated boron composite particles disclosed in this embodiment are the same as those in Example 1, with the only difference being that the amount of dopamine hydrochloride used is different. In this embodiment, the amount of dopamine hydrochloride used in step 3 is 0.75 g, and 0.98 g of B@PDA@Viton composite particles are finally obtained.
[0067] Example 5
[0068] The steps of the preparation method of fluororubber-coated boron composite particles disclosed in this embodiment are the same as those in Example 1, with the only difference being that the amount of Viton fluororubber used is different. In this embodiment, 0.04 g of Viton fluororubber is dissolved in 6 g of acetone, and finally 0.92 g of B@PDA@Viton composite particles are obtained.
[0069] Example 6
[0070] The steps of the preparation method of fluororubber-coated boron composite particles disclosed in this embodiment are the same as those in Example 1, with the only difference being that the amount of fluororubber used is different. In this embodiment, 0.06 g of Viton fluororubber is dissolved in 6 g of acetone to finally obtain 0.95 g of B@PDA@Viton composite particles.
[0071] Example 7
[0072] The steps of the preparation method of fluororubber-coated boron composite particles disclosed in this embodiment are the same as those in Example 1, with the only difference being that the reaction temperature of the coating process in Step 5 is different. In this embodiment, the fluororubber solution is added to the B@PDA dispersion obtained in Step 4 at 55°C, and finally 0.96 g of B@PDA@Viton composite particles are obtained.
[0073] Comparative Example 1
[0074] The difference from Example 1 is that the boron powder is not subjected to film removal and PDA coating, and the raw material is directly taken, and the method of the present invention is started from step 4. The remaining steps are the same as in Example 1, and finally 0.94 g of product is obtained.
[0075] Comparative Example 2
[0076] The difference from Example 1 is that the amount of dopamine hydrochloride used is 1.5 g, that is, the mass ratio of dopamine hydrochloride to the boron powder used is 1:1, and the remaining steps are the same as Example 1, and finally 0.97 g of product is obtained.
[0077] Comparative Example 3
[0078] The difference from Example 1 is that the amount of Viton used is 0.2 g, and the mass ratio of Viton to the B@PDA composite particles used is 1:5. The remaining steps are the same as those in Example 1, and 1.04 g of product is finally obtained.
[0079] The ignition and combustion performance of the composite particles prepared in Examples 1 to 6 and Comparative Examples 1 to 3 were tested, and the results are shown in the following table:
[0080]
[0081] As can be seen from the above table, the B@PDA@Viton composite particles prepared by the method of the present invention have a shorter ignition delay time and a higher combustion heat. Examples 1 to 6 reflect the effect of the raw material ratio on the ignition and combustion performance. In particular, the B@PDA@Viton composite particles in Example 1 have the lowest ignition delay time and the highest combustion heat, indicating that 0.60g dopamine hydrochloride and 0.02g Viton are the best preparation ratio. Example 7 reflects the effect of reaction temperature on ignition and combustion performance. High temperature and fast Viton precipitation speed will make the coating effect poor, which will eventually lead to a decrease in the ignition and combustion performance of the material.
[0082] In Comparative Example 1, because the boron powder was not de-filmed and PDA coated, the coating effect was poor and there was an oxide layer on the surface of the boron, resulting in poor ignition and combustion performance; it can be seen from Comparative Example 2 that when the content of dopamine hydrochloride was too high, the interaction between fluororubber and boron was affected due to the excessive thickness of the intermediate coating layer, so its ignition and combustion performance was also poor; in Comparative Example 3, when Viton was excessive, a similar conclusion was obtained. Therefore, Example 1 is the best raw material ratio, and the method of PDA modification to enhance the interaction between boron and fluorine in the present invention can significantly improve the combustion performance of boron powder, and the obtained B@PDA@Viton composite particles can replace boron powder and be used in solid propellants to significantly improve the energy performance of the system.
[0083] The preferred embodiments of the present disclosure are described in detail above in conjunction with the accompanying drawings; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0084] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0085] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A method for preparing B@PDA@Viton composite particles, characterized in that: The following steps are involved: Step 1, mixing boron powder with deionized water, stirring at 70-90° C. for 4-6 hours to obtain a boron powder dispersion; Step 2, adding tris(hydroxymethyl)aminomethane to deionized water to prepare a Tris buffer solution with a pH of 8 to 9; Step 3, adding dopamine hydrochloride and the boron powder dispersion prepared in step 1 to the Tris buffer solution prepared in step 2, stirring and reacting at room temperature for 12 to 24 hours, and then filtering and drying to obtain B@PDA composite particles; Step 4, adding the B@PDA composite particles obtained in step 3 into an organic solvent, stirring at room temperature for 20 to 30 minutes to obtain a B@PDA dispersion; Step 5: dissolve Viton fluororubber in a low boiling point solvent to obtain a Viton fluororubber solution, add the Viton fluororubber solution to the B@PDA dispersion obtained in step 4 at 45-55° C., stir and react for 4-7 hours, and obtain B@PDA@Viton composite particles by suction filtration and drying.
2. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: The particle size of the boron powder in step 1 is 1 to 10 μm.
3. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: The mass ratio of the boron powder to deionized water in step 1 is 1:(60-80).
4. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: The mass ratio of tris(hydroxymethyl)aminomethane described in step 2 to the micron boron powder used is 1:(8-17).
5. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: In step 3, the mass ratio of dopamine hydrochloride to boron powder is 1:(2-5).
6. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: The mass ratio of the B@PDA composite particles to the organic solvent in step 4 is 1:(40-60).
7. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: The organic solvent described in step 4 includes n-octane, n-heptane, n-decane, undecane and dodecane.
8. The method for preparing the B@PDA@Viton composite particles according to claim 1, characterized in that: The mass ratio of the Viton fluororubber to the low boiling point solvent in step 5 is 1:(100-300); the mass ratio of the Viton fluororubber to the B@PDA composite particles is 1:(10-50).
9. The method for preparing B@PDA@Viton composite particles according to claim 1, characterized in that: The low boiling point solvent described in step 5 includes acetone, ethyl acetate, methyl ethyl ketone, and tetrahydrofuran.
10. A B@PDA@Viton composite particle, characterized in that: The composite particles are prepared by the preparation method of the B@PDA@Viton composite particles described in any one of claims 1 to 9.